A Comparison of Changes in Pulmonary Flow Resistance in Healthy Volunteers Acutely Exposed to SO2 by Mouth and by Nose. Issue 1 (January 1966) - Speizer, F. E.; Frank, N. R.
Abstract : On separate occasions, healthy male volunteers were exposed either by nose or by mouth to one of two concentrations of sulphur dioxide, 15 and 28 p.p.m. Exposure to SO2 lasted 10 minutes. Pulmonary flow resistance (R1) was measured by the oesophageal catheter method, and the lung volume was measured by a modification of the gas-compression method; when SO2 was administered by nose, nasal flow resistance (Rn) was measured by means of a catheter placed in the posterior pharynx. The increase in R1 was greater when SO2 was administered by mouth than when it was administered by nose. Similarly, irritative symptoms of the posterior pharynx and chest were more common during exposure by mouth. These findings suggest that the mouth is less effective than the nose as an absorptive surface for SO2 .